Pengaturan Mutual Legal Assistance Dalam Hukum Internasional (Kasus Konfederasi Swiss-Indonesia) - Erica Febrianti; Josina Augustina Yvonne Wattimena; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Indonesia conducted Mutual legal Assistance (MLA) Agreement negotiations with the Swiss Federation on February 4, 2019 in Bern, Switzerland. Due to the MLA agreement, this is one of the access rights to track the assets of corrupt people hiding in Switzerland.Purposes of the Research: This article aims to identify the provision of mutual legal assistance in international legal instruments and the position of mutual legal assistance between two countries as an international legal instrument for restitution of state property. Methods of the Research: The method used in this study is the legal research method, a type of descriptive analysis, the sources of legal documents are primary legal documents, secondary legal documents, and legal documents. tertiary legal documents. Analysis of legal documents and methods of analyzing legal documents.Results of the Research: The results of the study show that the position of MLA (Mutual Legal Assistance) between the Republic of Indonesia and Switzerland as one of the efforts to return state assets, it can be concluded that the mutual legal assistance agreement between the Republic of Indonesia and Switzerland has not been effective, because it does not regulate the application of asset returns and the concept of MLA (Mutual Legal Assistance) in the agreement is only to facilitate the exchange of information related to assets, but follow-up actions to seize the assets of the perpetrators of corruption are left to the country requesting assistance, and until now, the Indonesian government does not yet have a legal umbrella in the form of separate laws regarding returns assets resulting from criminal acts, both corruption and other serious crimes.